Immunisation enrolment toolkit : for primary and secondary schools from 1 April 2018 - New South Wales. Ministry of Health (North Sydney, NSW : NSW Ministry of Health, 2018)
This toolkit has been developed to help primary and secondary schools to comply with their legal responsibilities under the NSW Public Health Act 2010.
Title from cover.
"Produced by Health Protection NSW, NSW Ministry of Health"--Cover verso.
Includes bibliographical references (page 14)
Also available online. Address as at 17/10/2018
Keywords: Vaccination of children -- New South Wales; Vaccination of children -- Law and legislation -- New South Wales; Immunization of children -- New South Wales; Australian